Pengembangan Masyarakat Islam dalam Sistem Dakwah - AS, Enjang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
Daâwah is awareness consfectus of human with dedication and the high commitment of their religion for developing prosperity of humans life and full with sense of justice. In applicate, for achieving that, can be done throught tathwir approach, that is the effort to empower or develop the quality of Islamic society that render khairu ummah based individual quality (khairul bariyyah). This condition will be achieved if iman, islam and taqwa transformated to value in individual, group, and social life, wuth so that the humans are placed on humanity position (fitri).